An Analysis of the Most Dominant Speech Act Used by the Teacher in EFL Classroom - Saidah, Saidah (Jurnal Ilmiah Pendidikan Profesi Guru, 2021)
The use of speech act in teaching and learning process of EFL classroom has been an interesting topic to be discussed. It is due to the distinct culture between the origin language and the target language. Therefore, the purpose of this study is to review some previous studies about the most dominant speech act used by the teacher in EFL classroom. The method used in this study is library research by using article of some previous researches to be analyzed. After the data are analyzed and concluded, the result of this study shows that the most dominant speech act used by the teacher in EFL classroom is directive which also indicated as student-centered model of classroom.Key words: EFL classroom, Pragmatics, Speech Act